The impact of counselling on anxiety and comorbid depression in patients with life-threatening illnesses in Hong Kong - ZHANG TONGYUAN, ZHANG TONGYUAN; ZULKARNAIN A. HATTA, PROF. DR. ZULKARNAIN A. HATTA (International Journal of Multidisciplinary Research and Studies, 2024)
For the most part, this variety of "female breast cancer incidence worldwide. Anxiety is a major problem for people with breast cancer and has devastating effects on their mental and physical well-being. Anxiety and depression levels among breast cancer patients change as their disease develops, a recent research found (McGregor & Antoni, 2009). Anxiety typically causes physical symptoms such as fatigue, sleeplessness, rapid heart rate, high blood pressure, stomach problems, restlessness, and a sense of helplessness (Sharpley et al, 2009). Multiple studies have shown that persons who suffer from chronic anxiety have a compromised immune system and other physiological regulatory processes (Segerstrom & Miller, 2004). The growing proportion of women who experience anxiety makes it all the more important to study effective treatments "a cancer diagnosis was made. Reason being: Chinese calligraphy "has the potential to be used as an intervention for anxiety reduction, and has been used for millennia as a spiritual activity to increase self-awareness and self-confidence. Almost all Western-style psychotherapy methods centre on therapeutic conversations between the therapist and patient. Regardless of the underlying theoretical framework, psychotherapy is primarily a client-centered and therapist-led kind of care that centres on building a trusting, respectful relationship between the two parties involved. The procedure usually starts with a discussion between the doctor and patient. The therapist provides a safe and encouraging space for the client to share their concerns in an uninhibited manner (American Psychological Association, 2017). Verbal "In individualistic societies, where people are encouraged to verbalise their feelings in times of distress, expressive therapies are common and have been proved to be successful. But in certain Asian societies, "It is considered rude and even childish to express negative feelings aloud or on one's face, especially wrath or sadness. There will be evidence that the calming effects of Japanese culture may be traced back to the country's collectivist social norms, which encourage members to suppress their emotions in public (Ehring, Caffier, Schnulle, Fischer, & Gross, 2010). Increasing emphasis on verbal expression may not be as helpful for people from these cultures since it may go counter to their values. It's crucial to consider the patient's cultural background and openness to alternative therapies while developing a psychotherapy treatment plan. Even though psychotherapy will continue to be a vocally mediated method, it would be beneficial to use nonverbal strategies to induce positive changes in populations not very receptive to verbal expressive treatment (Malchiodi, 2006). Studying the effects of Chinese calligraphy on "The major focus of this research is on people of Chinese ancestry who have been diagnosed with breast cancer.